Who is on the side of good? Values in Russian foreign policy - Lisiakiewicz, Rafał (Journal of Public Governance, 2018)
The author of this paper argues that the basic problem in relations between Russia and the West concerns political values shared by these entities in the area of international relations. This paper examines the problem on the three basic levels: (1) the basic paradigm of interpretation of international relations in Russia, i.e. realism; (2) the consequences of this approach for Russia’s place in international relations; and (3) the importance for Russia of economic cooperation with Western partners.